SPREADING AND TREATMENT OF DOGS’ TISSUE GROWTH PATHOLOGY - Dmytrenko, N. I.; Sherstiuk, L. M. (Scientific Progress & Innovations, 2020)
The spreading of tumors among dogs and cats in the town of Poltava was analyzed. In order to determine the spreading of neo-formations among dogs and cats, statistical data for the last two years were collected and processed in veterinary clinics of Poltava. Differential diagnostics of morphological types of some kinds of dog tumors was conducted. Morphological, cytological and histological structure of neoplasms was con-sidered. The problem of tumor growth is quite common among small dogs and cats. For the last two years, tumors were diagnosed in 98 dogs and 77 cats (56 % and 44%, respectively). Among dogs, 70 % of them were purebred. But a significant predisposition to tumors of certain types in a particular breed was not re-vealed. In most cases, (21.4 %) dogs were diagnosed with malignant mammary gland tumors. Those tumors were of different sizes and spread over one or more milk packets. Papillomatosis (18.4 %) is a quite com-mon pathology of tissue growth. The places of localization and placement of papillomas on the body of dogs and cats were outlined, and description of their appearance was given. The order of tumor germ formation was characterized. Depending on the symptoms and course of the disease, such diagnostic methods as palpa-tion, radiography, ultrasound diagnostics were used, and in some cases morphological and biochemical pa-rameters of blood were examined to determine the degree of metabolic disorders. Not only tumor was local-ly studied but also the degree of involvement of the surrounding tissues in pathological process. The reaction of local lymphatic nodes and the appearance and development of metastases were monitored with the help of ultrasound diagnostic device. Different treatment regimens of experimental animals’ papillomatoses were compared. It has been found out that including “Vincristine” preparation to the treatment regimen signifi-cantly reduces the term of treatment and gives the expressed therapeutic effect after the second injection, which results in gradual reduction of papillomas, their drying and rejection.